SOCIAL DILEMMA OF THE MAIN CHARACTER IN THE NOVEL THE HEIR BY KIERA CASS - Ryan Adi Nugroho; Henny Suharyati; Ade S Natawiria (Universitas Pakuan, 2020)
In this thesis, the problem discussed focuses on the influence of the social dilemma of the main character in the novel The Heir by Kiera Cass. Eadlyn's dilemma was a problem she faced in her own family that forced her to complete The Selection and her dream of becoming a royal ruler. This research uses descriptive analyst method, based on the psychological approach of ID, ego, super ego and research techniques based on library research. The results of the research prove that dilemma can influence the decision of the main character that makes the main character sacrifice her dreams to her parents for the sake of the kingdom rather than her own desires. The dilemma of exogenous factors experienced by the main character in the novel The Heir by Kiera Cass has a greater role in influencing decisions taken by the main character and it also affects the social life of the main character in the form of conflict between the main character and her family and changes in her nature, from being stubborn to being caring and compassionate.Keywords: dilemma, conflict, main character